ENT300 Fundamentals of Enterpreneurship Business Plan : Bae-Bee Store / Nur Hakiimah Binti Hasfa... [et.al] - Hasfa, Nur Hakiimah; Wan Zainaudin, Sharifah Nadia Nursyahirah; Adnan, Nur Afifah Nadzirah; Felixson, Jasmine (2014)
We have decided to form a partnership company with 4 shareholders. Each of the shareholders have been given specific job and task based on their experiences, knowledge and skills such as General Manager, Administrative Manager, Marketing Manager, Operational Manager, and Financial Manager. Each of our member is an expert in their own areas. As a company based on both product and service, each department have its own role and responsibilities in order to expend our business and achieve our company’s goal. As the head of the company, General Manager must possess the ability to control the company and set up the vision and mission of the company. Administration manager is important to encourage and increase sales revenue. As for Operational Manager, it is their duty to monitor company activities to ensure the business meet the customers' expectations. Financial plan is the most crucial aspect to improve company financial performance which was handled by the Financial Manager.